Inferior outcome after allogeneic transplant in first remission in high‐risk AML patients who required more than two cycles of induction therapy. Issue 8 (August 2015) - Lim, Sara J.; Lim, Matthew J.; Raptis, Anastasios; Hou, Jing‐Zhou; Farah, Rafic; Marks, Stanley M.; Im, Annie; Dorritie, Kathleen; Sehgal, Alison; Agha, Mounzer; Felgar, Raymond; Lim, Seah H.
<x xml:space="preserve">Abstract</x> While some patients with high‐risk acute myeloid leukemia (AML) require one or two cycles of induction chemotherapy to achieve a complete remission (CR), others require more than two cycles. We examined the outcomes of patients with high‐risk AML who received allogeneic HPC transplant in CR1. Forty five consecutive high‐risk AML patients in CR1 were included. All 45 patients had adverse cytogenetics, FLT 3 mutations, or secondary AML. Group A patients (n = 33) received one or two cycles, and Group B (n = 12) three or more cycles of induction chemotherapy. The patients were comparable in age, sex, white cell count at presentation, and time from diagnosis and from last chemotherapy to transplant. The 100‐day mortality rate was higher in Group B patients (50% vs. 9%, P = 0.006). They had a higher non‐relapse mortality (33% vs. 6%, P = 0.035) and a longer length of hospital stay from the day of stem cell infusion (median 21 vs. 20, P = 0.02; third quartile 22 vs. 28, P = 0.02). There was also a trend toward inferior event‐free survival and overall survival. High‐risk AML patients undergoing allogeneic transplant in CR1 after three or more cycles of induction chemotherapy have an inferior outcome and higher mortality when compared to those who only needed one or two cycles of induction chemotherapy. Novel strategies are needed to reduce the transplant‐related mortality in high‐risk AML patients needing more than two cycles of induction chemotherapy prior to allogeneic transplant in CR1. Am. J. Hematol. 90:715–718, 2015. © 2015 Wiley Periodicals, Inc.